Music Learning Theory by Edwin E.Gordon - Yuliya Poplavska-Melnychenko (Pedagogical Discourse, 2013)
The article reveals the specifics of a theory of music learning, depicted by the well-known American researcher and teacher Edwin E. Gordon. It also shows the significance and the implication of the term «audiation», invented by the researcher, as well as it determines «audiation» types, as well as the stages of preparation for audiation, here the comparison between the processes of attaining music information and language information is presented and their common grounds are emphasized. Moreover, it discloses the relationship between this theory and other methods of children's early musical development. Based on this material the conclusion has been made that the mentioned theory is unique in its attempts to apply psychological priniciples towards teaching and learning music and also that it can be of paramount benefit in music education.